EXPLORING INNOVATIVE APPROACHES TO CURRICULUM DESIGN AND DEVELOPMENT (Academicia Globe: Inderscience Research, 2024)
In the rapidly evolving landscape of education, traditional curriculum models are becoming insufficient to meet the diverse and complex needs of today’s learners. Innovative approaches to curriculum design and development are gaining traction as educational institutions seek to improve student engagement, foster critical thinking, and prepare learners for real-world challenges. This article explores various innovative strategies in curriculum design, including competency-based education, interdisciplinary curricula, and the integration of technology. The effectiveness of these approaches is analyzed in light of current educational trends, with an emphasis on how innovation can create more flexible, inclusive, and student-centered learning environments. The article also highlights challenges faced in the implementation of these methods and suggests future directions for research and practice.